Contribution of osmotic suction to shear strength of unsaturated high plasticity silty soil - Leong, Eng-Choon (2020)
The engineering behaviour of unsaturated soils is affected by suction. It is widely accepted that soil suction consists of two major components: matric and osmotic suctions. Matric suction is associated with the capillary effects whereas osmotic suction is associated with the salt content of the pore water. Soil suction has been incorporated as “effective” stress or suction stress when describing the engineering behaviour of unsaturated soils. Usually, the suction component that is incorporated is matric suction while the contribution of osmotic suction is seldom investigated. In this paper, the contribution of osmotic suction to shear strength of unsaturated soils is investigated through unconfined compression tests on three series of compacted soil prepared using distilled water and sodium chloride solution. Specimens were prepared at three water contents corresponding to dry densities at dry of optimum, optimum and wet of optimum on the standard Proctor compaction curve. Series one and two consist of specimens compacted using distilled water and sodium chloride solution, respectively. In series three, one half of the specimen was compacted using distilled water and the other half compacted using sodium chloride solution. Unconfined compression tests were conducted on the soil specimens at various elapsed times after compaction to allow for ionic equilibrium due to the osmotic gradient in the third series of soil specimens. The test results show soil specimens have similar strength at each compaction water content regardless of elapsed time and type of pore water. No effect of osmotic suction or osmotic suction gradient on shear strength of the compacted soil specimens was found. It was concluded that the salt content of the pore water affects the soil structure of clayey soils and does not act like matric suction. Hence, matric suction should be measured in order to quantify the engineering behaviour of unsaturated soils.